Total Ankle Replacement with Built-in Antibiotic Spacer: A Paradigm Shift in the Management of Infected Ankles - Trapper Lalli MD; Abigail Smith MD; Reyanne Strong MD; Nathaniel Koutlas MD; James O. Sanders MD (Foot & Ankle Orthopaedics, 2024)
Introduction/Purpose: Infection of an ankle fracture is a devastating complication that can lead to chronic pain, limited motion or amputation. Traditional treatment strategies after infection involve aggressive surgical debridement, implant removal and prolonged antibiotic therapy. Non-anatomic cement spacers for the tibiotalar joint have previously been described with mixed results. Articulating spacers have shown improved outcomes and may be used as definitive treatment. Currently, there are no prefabricated TAR spacers on the market. The use of 3D printing to create custom implants is emerging, however, there is a paucity of literature regarding their use. We present a case of post-infectious ankle arthritis in 14 year old patient treated with a 3D printed total ankle replacement with built in antibiotic spacer (TAR-AS). Methods: A CT scan was performed in accordance with computer aided design (CAD) parameters. Bilateral lower extremities were scanned to allow the unaffected side to be mirrored and be the basis for implant design. Slice spacing less than 1.25mm with pixel size of 0.5mm. The studies were in DICOM files and within a timeframe where no significant change in patient anatomy had occurred. The implants were fabricated by selective laser melting (SLM) of cobalt chrome alloy (CoCrMo) by Restor3d (Durham, NC). Our design incorporated a stacked gyroid component to facilitate antibiotic cement impregnation. In terms of surgical technique, the custom TAR-AS followed a similar approach to a patient specific TAR procedure. Prior to implantation, the gyroid component of the TAR-AS was filled with Simplex bone cement with tobramycin (Stryker). Results: At six months postoperatively, our patient reported no limitation in activities. AOFAS scores improved from 46/100 preoperatively to 83/100 at six months postoperatively. Radiographic parameters showed no signs of implant failure, loosening or change in alignment. Intraoperative cultures remained negative. Conclusion: We present a case demonstrating the utilization of 3D generated prostheses for treatment of post-infection ankle arthritis. The TAR-AS represents a significant advancement in the management of ankle infections. This innovative approach combines the benefits of joint replacement and continued antibiotic elution. With further research and continued technological advancements, the TAR-AS has the potential to become the gold standard for the treatment of infected TAR. Despite the promising results, challenges remain in the implementation of TAR-AS. Long term follow up studies are needed to evaluate the durability and longevity of the implant. Total ankle with built in antibiotic spacer Superior view of tibial tray with antibiotic cement packed in gyroid